PENINGKATAN KAPASITAS DAN KUALITAS PENGERINGAN,PEWARNAAN DAN PENGEMBANGAN DESAIN PRODUKKERAJINAN TOPENG DAN BATIK KAYU UNTUKMENINGKATKAN PASAR EKSPOR DAN PASAR DOMESTIK - dan Sumino, Yuni Pratiwi, Sukoco, (Universitas Negeri Yogyakarta, 2013)
Crafting Industry not easy to fall by economic crisis. So that have tobe developed to become strength of people economics. In Bobung Putat,Pathuk, Gunungkidul almost all its resident work as worker of wood batikand mask. Crafting of wood batik and mask have become home industry andas especial living to society. Mask product and wood batik of Bobung havecan penetrate market export and domestic market. For the market of exportingBrasilia, Singapore, India, Canada, Belgia, Malaysia, Australian,Japan, New Selandia, and America is export market from mask product andwood batik of Bobung. Solo, Bali, Surabaya, Medan, Bandung, Bogor,Batam and Jakarta is domestic market from mask product and wood batik ofBobung. Total Sale per annum reach two billion rupiah moreConstraint which often met by worker cannot fulfill order of causedby order limitation of dryer machine. In this time worker use oven havingsmall capacities and still traditional without regulator of spreading of goodheat and without regulator of time and temperature. Quality of product isnot maximal, still have content irrigate and easy to hit mushroom. ProductDesain of monoton and less inovatif, still use colourant of sintetis withunfavourable coloration technique.To increase product quality and capacities with dryer machineengineering with pipe spreading of good heat, with timer and regulator oftemperature. To increase product variation with training of desain and toincrease the quality of colour with training of coloration technique andusage of natural colour. New Oven can improve capacities produce twicethe either from previously